Laparoscopic Repair of Traumatic Intraperitoneal Bladder Rupture: A Case Series - Yoonjung Heo; Dong Hun Kim (Journal of Acute Care Surgery, 2021)
Bladder injury is uncommon in blunt abdominal trauma. The injury can be life-threatening if not treated properly. Thus, timely and accurate diagnosis is critical. Traumatic intraperitoneal bladder rupture (TIBR) can be managed laparoscopically in patients who are hemodynamically stable. In this case series, we present 3 patients who underwent laparoscopic repair of TIBR performed by a single surgeon. In addition, we address useful technical tips that would facilitate the generalized use of laparoscopy for treating TIBR.